Comparison of Parameters from Heidelberg Retina Tomographs 2 and 3 - Gabriele, Michelle L. (2007)
PURPOSE: To compare stereometric parameters and classification results from the Heidelberg Retina Tomograph version 2 (HRT2); HRT3; and HRT3 Glaucoma Probability Score (GPS), an automated method of obtaining optic nerve head analysis without the need for manual definition of disc margin. DESIGN: Retrospective cross-sectional study. PARTICIPANTS: Five hundred four eyes from 281 consecutive subjects (glaucoma, glaucoma suspect, and healthy) evaluated in a glaucoma clinic. METHODS: All participants had HRT2 scanning of the optic nerve head. Inclusion criteria were scans with good centration and focus, even illumination, an overall quality score by HRT3 of acceptable or better, and standard deviation < 50 µm. A Bland–Altman analysis was used for the comparison of HRT2 and HRT3. From these results, calibration equations were determined to permit conversion of the measurements between devices. The agreement between HRT2 and HRT3 Moorfields regression analysis (MRA) and HRT3 GPS classification methods was measured using κ statistics. MAIN OUTCOME MEASURES: Heidelberg Retina Tomograph version 2 and HRT3 stereometric parameters, MRA, and global GPS. RESULTS: There was a statistically significant difference between HRT2 and HRT3 global disc area, rim area, cup area, rim volume, cup volume, height variation contour, and retinal nerve fiber layer cross-sectional area stereometric parameters. All of those parameters were smaller using HRT3, due to a manufacturer-reported horizontal scaling error of 4% in HRT2 that was corrected in HRT3. κs for agreement were 0.60 between classifications (within normal limits, borderline, and outside normal limits) of MRA by HRT2 and HRT3 and 0.47 between HRT3 MRA and GPS. CONCLUSIONS: The HRT3 generally provided smaller stereometric disc measurements than HRT2. There was no clear conversion between HRT3 and GPS parameters, as the 2 methods for measuring the stereometric parameters differ.